PGPR‐mediated induction of systemic resistance and physiochemical alterations in plants against the pathogens: Current perspectives - Meena, Mukesh; Swapnil, Prashant; Divyanshu, Kumari; Kumar, Sunil; Harish; Tripathi, Yashoda Nandan; Zehra, Andleeb; Marwal, Avinash; Upadhyay, Ram Sanmukh (Journal of basic microbiology, 2020)
Plant growth‐promoting rhizobacteria (PGPR) are diverse groups of plant‐associated microorganisms, which can reduce the severity or incidence of disease during antagonism among bacteria and soil‐borne pathogens, as well as by influencing a systemic resistance to elicit defense response in host plants. An amalgamation of various strains of PGPR has improved the efficacy by enhancing the systemic resistance opposed to various pathogens affecting the crop. Many PGPR used with seed treatment causes structural improvement of the cell wall and physiological/biochemical changes leading to the synthesis of proteins, peptides, and chemicals occupied in plant defense mechanisms. The major determinants of PGPR‐mediated induced systemic resistance (ISR) are lipopolysaccharides, lipopeptides, siderophores, pyocyanin, antibiotics 2,4‐diacetylphoroglucinol, the volatile 2,3‐butanediol, N‐alkylated benzylamine, and iron‐regulated compounds. Many PGPR inoculants have been commercialized and these inoculants consequently aid in the improvement of crop growth yield and provide effective reinforcement to the crop from disease, whereas other inoculants are used as biofertilizers for native as well as crops growing at diverse extreme habitat and exhibit multifunctional plant growth‐promoting attributes. A number of applications of PGPR formulation are needed to maintain the resistance levels in crop plants. Several microarray‐based studies have been done to identify the genes, which are associated with PGPR‐induced systemic resistance. Identification of these genes associated with ISR‐mediating disease suppression and biochemical changes in the crop plant is one of the essential steps in understanding the disease resistance mechanisms in crops. Therefore, in this review, we discuss the PGPR‐mediated innovative methods, focusing on the mode of action of compounds authorized that may be significant in the development contributing to enhance plant growth, disease resistance, and serve as an efficient bioinoculants for sustainable agriculture. The review also highlights current research progress in this field with a special emphasis on challenges, limitations, and their environmental and economic advantages.